2012
DOI: 10.2807/ese.17.27.20209-en
|View full text |Cite
|
Sign up to set email alerts
|

First report of sandfly fever virus infection imported from Malta into Switzerland, October 2011

Abstract: We report the first documented cases of sandfly fever virus infection in travellers returning from Malta to Switzerland in autumn 2011. These cases illustrate the importance of considering sandfly-borne viral infection in the differential diagnosis of febrile patients from the Mediterranean island Malta. Raising awareness among physicians is relevant especially now at the beginning of the summer tourist season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Like other arboviruses, most TOSV infections in humans are asymptomatic [6]. So far, 864 symptomatic human cases (834 autochthonous and 30 imported) have been reported in residents of different Mediterranean countries and in tourists and travelers returning from endemic regions [7][8][9][10].…”
Section: Overview On Toscana Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other arboviruses, most TOSV infections in humans are asymptomatic [6]. So far, 864 symptomatic human cases (834 autochthonous and 30 imported) have been reported in residents of different Mediterranean countries and in tourists and travelers returning from endemic regions [7][8][9][10].…”
Section: Overview On Toscana Virusmentioning
confidence: 99%
“…Seroprevalence studies demonstrate that human populations are exposed to TOSV in Italy, Spain, France, Portugal, Turkey, Malta, Cyprus, Greece, Croatia, Bosnia and Herzegovina, Kosovo, Bulgaria, Tunisia, and Algeria [7,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Together, the results of serological surveillance studies and case reports showed that the TOSV geographic distribution is much wider than believed a decade ago; in particular, the presence of TOSV has been recently documented in North Africa and the Balkan countries [31,32,[34][35][36] (Figure 2).…”
Section: Epidemiology Of Toscana Virusmentioning
confidence: 99%
“…Sandfly fever is also very important for travelers' health; imported cases are reported in the literature from non-endemic areas due to travelling [3][4][5]24]. In 1997, a case of travel associated SFSV infection presenting as meningitis in female patient, after a vacation to Turkey, was reported by Becker et al [5].…”
Section: Sandfly Fever In Non-endemic Areas Travelers' Health and MImentioning
confidence: 99%
“…Other cases with febrile disease after returning to Switzerland from Malta found to have sandfly fever. One of the patients was lucky to present with insect bites and rash giving a clue about vector-borne travel-related disease and detected for phlebotomus fever which was found to be positive [3].…”
Section: Rvfv-dq375430mentioning
confidence: 99%
See 1 more Smart Citation